2021
DOI: 10.1002/solr.202100506
|View full text |Cite
|
Sign up to set email alerts
|

Dopant‐Free Ternary Conjugated Polymeric Hole‐Transporting Materials for Efficient Inverted Planar Perovskite Solar Cells

Abstract: Perovskite solar cells (PSCs) have achieved an outstanding power conversion efficiency (PCE, up to 25.5%) due to the unique optoelectronic properties of perovskites, thus being comparable to the commercialized silicon-based solar cells (%26%). [1] Among the reported high-performance PSCs, most studies have focused on the traditional (ni-p) structures to improve the efficiency by optimizing cell architectures and perovskite and interfacial materials. The conventional n-i-p structure of a PSC features the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…Hao and Li et al reported two D–A 1 -D–A 2 type polymeric HTMs, PTPDTBT and PDPPTBT, comprising of the benzothiadiazole (BT) unit (A 1 ), thieno[3,4- c ]pyrrole-4,6-dione (TPD) or diketopyrrolopyrole-flanked alkyl-thiophene (DPP) moieties (A 2 ) and thiophene unit (D) as dopant-free HTMs in the inverted PSCs. 98 The PDPPTBT-based device exhibited an excellent PCE of 18.1%, which was higher than that of the PTPDTBT-based device (16.4%) and significantly exceeded the 12.6% efficiency of the well-known PEDOT:SS-based device. More importantly, the PDPPTBT-based device maintained 71% of its initial PCE after 500 h in ambient air with an RH of 60%, while the PCE of the PEDOT:PSS-based device decayed to zero after 100 h.…”
Section: Perovskite Materialsmentioning
confidence: 81%
“…Hao and Li et al reported two D–A 1 -D–A 2 type polymeric HTMs, PTPDTBT and PDPPTBT, comprising of the benzothiadiazole (BT) unit (A 1 ), thieno[3,4- c ]pyrrole-4,6-dione (TPD) or diketopyrrolopyrole-flanked alkyl-thiophene (DPP) moieties (A 2 ) and thiophene unit (D) as dopant-free HTMs in the inverted PSCs. 98 The PDPPTBT-based device exhibited an excellent PCE of 18.1%, which was higher than that of the PTPDTBT-based device (16.4%) and significantly exceeded the 12.6% efficiency of the well-known PEDOT:SS-based device. More importantly, the PDPPTBT-based device maintained 71% of its initial PCE after 500 h in ambient air with an RH of 60%, while the PCE of the PEDOT:PSS-based device decayed to zero after 100 h.…”
Section: Perovskite Materialsmentioning
confidence: 81%
“…The above advantages make DPP and IID as the excellent building blocks for many applications like polymer semiconductor materials. [26][27][28] As we all know, the introduction of fluorine atoms in organic and polymer semiconductor materials can effectively promote charge transport and absorption properties in some cases because the noncovalent interactions and hydrogen bonding interactions (F⋯H, F⋯S, and F⋯π) could be utilized to rigidify the conjugated backbones. [29][30][31][32] Hence, a suitable strategy is to combine the advantages of DPP and IID unit via copolymerization as well as fluorination, endowing a potentiality of an efficient visible/NIR hydrogen evolution.…”
Section: Synthetic Strategymentioning
confidence: 99%
“…4–6 Numerous studies have focused on developing various kinds of efficient HTMs including inorganic materials, 7–9 organic small molecules, 10–12 and polymers. 13–16 Among them, triarylamine (TAA)-based polymeric HTMs ( e.g. , poly-TPD and PTAA) are widely used in inverted PSCs owing to their advantageous features; those HTMs afford smooth thin-film morphology on the bottom electrode, excellent electrical properties, and well-matched frontier energy levels with perovskite.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Numerous studies have focused on developing various kinds of efficient HTMs including inorganic materials, [7][8][9] organic small molecules, [10][11][12] and polymers. [13][14][15][16] Among them, triarylamine (TAA)-based polymeric HTMs (e.g., poly-TPD and PTAA) are widely used in inverted PSCs owing to their advantageous features; those HTMs afford smooth thin-lm morphology on the bottom electrode, excellent electrical properties, and well-matched frontier energy levels with perovskite. [17][18][19][20][21] However, despite their benets, the strong hydrophobicity of TAA-based polymeric HTMs oen prevents the corresponding HTL lms from being completely wetted by perovskite precursor solutions, resulting in the formation of nonuniform perovskite layers.…”
Section: Introductionmentioning
confidence: 99%